Relapse of Diffuse Large B‐Cell Lymphoma as Painless Masses in the Abdominal Wall Muscles: A Rare Case Report - Somar Mansour; Seif‐Aldin Abdul Rahman; Majd Mansour; Ali Afif; Raghad Hasan; Nader Abdullah; Zuheir Alshehabi (Cancer Reports)
ABSTRACT Background The most frequent type of non‐Hodgkin lymphoma (NHL) is diffuse large B‐cell lymphoma (DLBCL). Although lymph nodes are the most commonly affected organs compromising 70% of DLBCLs, only 5% of extranodal lymphomas represent skeletal muscle involvement. Specifically, abdominal wall muscle involvement is rare and there are only a few reported cases of DLBCL with this type of muscle involvement. Painful abdominal mass was the main presenting symptom in these reported cases. Case We are reporting a relapsed DLBCL with abdominal wall muscle involvement in a 65‐year‐old male, presenting with a discomfort and heaviness sensation in the right iliac region with no associated pain. Conclusion A rare case of DLBCL with recurrence in the abdominal wall muscles as painless masses was reported in this case report. To our knowledge, it is considered the fourth reported in the medical literature. It shows the importance of the diagnostic process that combines imaging with histological examination and immune stains for accurate diagnosis.